SPEKTROSKOPI FT-IR (FOURIER TRANSFORM INFRARED) SEBAGAI PEMBEDA STRUKTUR SENYAWA KOMBINASI SIPROFLOKSASIN SALISILAT BENTUK GARAM TERHADAP BENTUK PERSENYAWAAN NETRAL - Alyaa Khairunnisa, Nianda
Compounds formed between molecules can be composed of nonionic (noncovalent) interactions to form neutral compounds or through ionic interactions to form salts. This intermolecular interaction is important to be studied and analyzed further. In this experiment, the interaction that composes the combination compound between ciprofloxacin base and salicylic acid can be reviewed in detail using the FT-IR (Fourier-Transform Infrared) analytical spectroscopy instrument. The spectrum detected in the FT-IR can provide information regarding the shift in the absorption band of the typical groups that make up the cipro-salicylate combination compound, such as the OH, N-H, C=O, and C-O groups. These groups have different absorption peak values in the CIP-SA 1:1 and CIP-SA 1:2 combination compounds to the original compound. The shift in the absorption peak that occurs can refer to the molecular interactions between ciprofloxacin base and salicylic acid. Neutral compounds can be seen from the shift of the N-H group at wave number 1627.63 cm- 1 in CIP-SA 1:1 and 1616.06 cm- 1 in CIP-SA 1:2, as well as the shift of the O-H group at 3401.82 cm- 1 in CIP-SA 1:1 and 3394.1 cm- 1 in CIP-SA 1:2 which indicates the form of supramolecular heterosynthon of O-H. . .N. Meanwhile, the salt formation can be seen from the shift of the C=O group at 1716.34 cm- 1 in CIP-SA 1:1 and 1700.91 cm- 1 in CIP-SA 1:2, as well as the shift of C-O group at 1338,36 cm- 1 in CIP-SA 1:1 and 1253,5 cm- 1 in CIP-SA 1:2 due to the interaction between the carboxylic group in salicylic acid and N atom in the ciprofloxacin piperazine ring. To ensure the data obtained from the FT-IR spectrum, supporting data is needed using other analytical methods such as electrothermal, DSC, and PXRD. The analysis results using these supporting instruments may lead to the hypothesis of the formation of cipro-salicylate in the form of neutral compounds and salts obtained from FTIR.